The Relationship between Family Support and Breast Self-Examination (BSE) in Breast Tumor Patients - Azza Nabila, Amira; Indriyani, Indriyani; Pratiwi, Ratih; Mitayani, Mitayani (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Introduction. In the management of both benign and malignant breast tumors, early detection via breast self-examination (BSE) is essential. It is thought that family support is crucial in promoting BSE behavior. Finding out how family support and breast self-examination (BSE) in patients with breast tumors relate to one another is the goal of this study. Methods. Cross-sectional is a study used in this study with an analytic observational method. The research sample was taken using a total sampling technique, which included all breast tumor patients who met the inclusion criteria at the surgical clinic of Muhammadiyah Hospital Palembang, totaling 32 respondents. Results. It was found that the majority of respondents suffered from malignant breast tumors (breast cancer), with 23 individuals (28.13%). Meanwhile, 9 other individuals had benign breast tumors (71.87%). Most of the respondents received family support categorized as adequate or insufficient, with their Breast Self-Examination (BSE) behavior also categorized as adequate or insufficient. The analysis revealed a p-value of 0.000 and an odds ratio (OR) of 27.00. Conclusion. It can be concluded that there is a significant relationship between breast tumor patients' behavior and family support, with those who received family support having a 27-fold higher likelihood of engaging in breast self-examination than those who did not.